Validation of the cross-cultural dementia screening test in Alzheimer’s disease and Parkinson’s disease - Delgado-Álvarez, Alfonso; Delgado-Alonso, Cristina; Goudsmit, Miriam; García-Ramos, Rocío; Gil-Moreno, María José; Valles-Salgado, María; Díez-Cirarda, María; Zamarrón-Cassinello, María Dolores; Matías-Guiu, Jorge; Matias-Guiu, Jordi A. (Frontiers in Psychology, 2023)
Objective: The Cross-Cultural Dementia (CCD) is a new screening tool to evaluate cognitive impairment based on a cross-cultural perspective to reduce the bias of education, and language and cultural differences. We aimed to evaluate the diagnostic properties of the CCD in Spaniards for the assessment of patients with Alzheimer’s disease in mild cognitive impairment (AD-MCI) and mild dementia stages (AD-D) and patients with mild cognitive impairment associated with Parkinson’s disease (PD-MCI). Method: Sixty participants with AD (50% MCI) and thirty with PD-MCI were enrolled. Each clinical group was compared against a healthy control group (HC) with the same number of participants and no significant differences in age, education, and sex. A comprehensive neuropsychological test battery and CCD were completed. Intergroup comparisons, ROC curves, and cut-off scores were calculated for the study of diagnostic properties. Results: Intergroup differences were found in accordance with the cognitive profile of each clinical condition. Memory measures (Objects test) were especially relevant for the classification between AD and HC. Memory and executive function scores (Sun-Moon and Dots tests) were useful in the case of PD-MCI and HC. Furthermore, CCD described differences in executive functions and speed scores comparing AD-MCI and PD-MCI. Correlations between standardized neuropsychological tests and CCD measures supported the convergent validity of the test. Conclusions: CCD showed good discrimination properties and cut-off scores for dementia and extended its application to a sample of prodromal stages of AD and PD with mild cognitive impairment.